STRATEGI DPMPTSP DALAM MENINGKATKAN JUMLAH PENDAFTARAN NOMOR INDUK BERUSAHA (NIB) BAGI UMKM DI KOTA BLITAR - Audy Rizky Titania; Talitha Alesia Naifah Zayyan; Mohammad Rifan; Magda Faradiba M.A (Program Pasca Sarjana Universitas Garut, 2025)
Micro, Small and Medium Enterprises (MSMEs) are pillars of the regional economy, including in Blitar City. Many MSME players do not yet have a Business Identification Number (NIB), while NIB is important as an official identity that supports access to financing, training, legal protection, and business development. This study aims to examine the strategy of Blitar City DPMPTSP in increasing NIB registration by MSMEs. The method used is descriptive qualitative through interviews, documentation, and observation, with SWOT analysis to assess internal and external factors. Results show the main strategies include utilizing the OSS system, ball pick-up program, collaboration with the private sector, and social media. Strengths lie in easy access to services, while weaknesses include low digital and legal literacy. Opportunities come from the support of MSME institutions and associations, while threats come from business resistance and limited infrastructure. The research recommends intensive education and mentoring to strengthen the legality and competitiveness of MSMEs.